The role and need for psychological support in the treatment of adolescents and young people suffering from type 1 diabetes - Małachowska, Magdalena; Gosławska, Zuzanna; Rusak, Ewa; Jarosz-Chobot, Przemysława (Frontiers in Psychology, 2023)
Psychological support might be perceived as one of the most important factors in the process of treatment of people suffering from diabetes type 1, especially when it comes to such vulnerable groups as adolescents and young people. Presented problems arising from extreme pressure put on young patients, high expectations and specific limitations connected with diabetes often reflect in negative well-being and affect patients’ behaviour, which results in lower self-esteem, mood swings, depression or even eating disorders. Therefore, the need for more holistic approach to the treatment of diabetes and caring about psychological support can be observed, which may contribute to better functioning and management of the disease. Differentiation of certain approach methods such as PA Positive Approach discussed in the text may help young patients in motivation and coping with their disease as well as accepting limitations caused by diabetes type 1. This would decrease the risk of potential revolt against medical recommendations, common for patients at mentioned age and help to raise awareness of the problem. Maintaining life balance through undertaking regular physical activities and being open to new strategies such as telenursing can also result in improvement of glycaemic control. Presented studies have proven the great effectiveness of personalized care adjusted to the patient with psychological support being a part of it and the invaluable role of education in diabetes, which refers not only to typical procedures such as calculation of appropriate insulin dose but also invention of effective coping mechanisms which also influence patients’ performance and well-being.